Evaluating the role of environmental advertising on the use of eye movements towards the brand - Seyed Hamid Mir Motahari; Sina Nematizadeh; Seyed Abbas Heydari (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to evaluate the role of environmental advertising on the use of eye movements towards the brand. The current research is applicable in terms of the goal and mixed (qualitative-quantitative) in terms of the method of data analysis. The statistical population in the qualitative section includes a group of restaurant chain experts (university professors, executive managers, and consultants), sampling continued with the purposeful method until reaching theoretical saturation (15 interviews). In the quantitative phase, chain restaurant managers were considered as the community among whom 384 people were picked up based on stratified random sampling. The data collection tool in the qualitative phase of the research was unstructured interviews with experts; and in the quantitative phase, a researcher-made questionnaire consisting of 74 items. In order to analyze the data, Maxqda software was used in the qualitative phase, and SPSS and SmartPLS software in the quantitative phase. According to the obtained results, the hypothetical relationships of the model were tested and confirmed. In this research, in the causal conditions (advertising content, environmental advertising quality, and advertising features); main contextual factors (advertising slogan, billboard elements, and analysis of customers' eye movements); intervening conditions (online advertising, advertising costs, advertising through means, and mass communication); core categories (the state of environmental advertising, the development of the impact of advertising, and effective advertising on customers' intentions); strategies (attractions of advertising message, evaluation of environmental advertising selection process); and three categories of competitive advantage, value creation, and promotion of strategic marketing decisions are classified as the consequences of environmental advertising based on the use of eye tracking. Extended Abstract Introduction Today, as consumers, we are exposed to hundreds of advertisements every day on television, newspapers, magazines, yellow pages, retail advertisements and websites, and in addition to these implicit advertisements in the form of Classification of products in stores and homes, visual messages on vehicles, road signs, food packaging in restaurants, uniforms of service providers, t-shirts, CDs and Electronic devices attract our attention (Niehorster et al, 2017), and the eyes, when searching and deciding to choose products and brands, guide consumers among the shelves and aisles of stores, shopping centers, and websites; all of which are related to "visual marketing"; that is, commercial and non-commercial companies use visual signs to communicate with consumers with the aim of creating and maintaining mutually beneficial relationships (Kong et al, 2019). If it is true that "observation equals confidence" and "confidence equals purchase", it is important that management is based on what the consumer sees. This issue is increasingly recognized in commercial activities (Guitart et al, 2018). The conducted research shows how the aspects and dimensions of the advertisement and the purpose of the advertisement to interact with the visitor affect the visual behavior and the amount of attention given to different parts of an advertisement (Marois et al, 2021). Eye tracking is the process of measuring attention (gaze) or the movement of an eye in relation to the head (Hosp et al, 2020). Eye tracking is a tool for measuring eye position and movements, which can be a useful method for analyzing behavior and cognition (Muñoz-Leiva et al, 2019). By using the eye tracking technique, behavioral evidence can be obtained (Guitart et al, 2018). Eye tracking is very sensitive to the processes of attention and alertness, and this technique can be used to improve teaching and learning (Javora et al, 2021) and the effectiveness of advertisements, video and graphic images (Niehorster et al, 2017). Considering that eye tracking can compensate for the market research that cannot be obtained through self-reporting methods, the main question of the present research has been raised as follows: how is the effective model of environmental advertising based on the use of eye tracking drawn? Theoretical literature Ambient advertising: ambient advertising includes advertisements used in unusual, noteworthy and unexpected places, often with unconventional and innovative methods, as well as new performances - performances appear to the audience for the first time. Eye tracking: Eye tracking in advertising means measuring and calculating the point at which the human eye is staring, and in other words, the scientific study of eye movements and activities in two-way interaction with the surrounding environment is called tracking (Kimasi et al., 2019). Mousavi & Fadaei (2022) in a study aimed at commercial advertisements of chain stores, found that variables of price, security and trust, digital marketing environment, product characteristics and ease of purchase had a significant effect on commercial advertisements of chain stores in the evolution of digital marketing literacy, and variable of promotional offers have not been effective. Marois et al, (2021) reported in a study aimed at real-time mobile eye tracking for support systems that the use of eye tracking in mobile should provide more reliable data than using a fixed device. According to them, the use of intelligent eye tracking systems can effectively help increase efficiency in security and services by showing people's decisions. Research methodology The present study is considered to be of the fundamental type in terms of its purpose, and mixed (qualitative and quantitative) in terms of the data collection method. The research community, in the qualitative dimension, includes experts in the field of marketing and business, and in the quantitative dimension, it includes managers and experts in the field of marketing and advertising. In the qualitative part, based on the selection of data-based theory, non-random sampling carried out and 15 interviews were conducted; that from the 11th interview onwards, theoretical saturation occurred, which continued until the 15th interview to be sure. In the quantitative section, taking into account the maximum variance and error level of 5%, 90 people were identified, and in order to increase the return rate of the questionnaire and facilitate the research, more than 100 questionnaires were distributed electronically. Out of this number, 86 people completed the questionnaire and this number was the basis of analysis and hypothesis testing. In the qualitative phase, an interview tool was used, and in the quantitative part, a researcher-made questionnaire tool was used. In order to analyze the data, Maxqda software was used in the qualitative phase, and SPSS and SmartPLS software in the quantitative part. Research findings In the presented model, three categories of advertising content; quality of Ambient advertising, and advertising features are experimental factors that can create the causal conditions of Ambient advertising based on the use of eye tracking. The main contextual factors of Ambient advertising are determined based on the use of eye tracking also include advertising slogans, billboard elements, and customers' eye movement analysis. Three categories of online advertising of advertising cost, advertising through means, and mass communication are considered as categories of intervening conditions according to Ambient advertising based on the use of eye tracking. The central categories of Ambient advertising based on the use of eye tracking in this model include three categories of Ambient advertising status, development of advertising influence, and effective advertising on customers' intentions. According to the results obtained in this model, three categories of advertising message attractions, evaluation of target Ambient advertising selection process, and advertising based on customers' taste have been included as strategies according to the central categories of Ambient advertising based on the use of eye tracking. According to open coding, the concepts related to the consequences of the model have been extracted, then according to the back and forth movement between the themes and concepts, the main categories have been extracted and named, and accordingly, the consequences are divided into three parts related to the competitive advantage, value-creating, and promotion of strategic marketing decisions are classified as the consequences of Ambient advertising based on the use of eye tracking. Discussion and conclusion The results obtained from the coefficients of the structural equations based on the effect of integrated advertising management on the advertising structure show that the value (t = 35.66) for this parameter (according to the 5% error rule in the region of rejecting the null hypothesis for values ​​outside the range of 1.96 to 1.96 of each parameter of the model) is out of the estimated range. Therefore, it can be stated that the first hypothesis of the research; the integrated advertising management has a positive effect on the advertising structure, is confirmed with 95% certainty. The result of this hypothesis is consistent with the research results of Boban et.al, (2020) and Rezabakhsh (2017). Based on the results of these researches, in today's competitive market environment, advertising companies have increasingly faced the challenges of good communication with customers in order to be able to introduce their new products and services to the market faster than their competitors. The results obtained from the coefficients of structural equations based on the effect of integrated advertising management on service delivery processes show that the value (t = 5.68) for this parameter is out of range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the research results of Pelsmackera & et al, (2019) and Casado-Aranda et al, (2023). The results obtained from the coefficients of structural equations based on the effect of integrated advertising management on Ambient characteristics show that the value (t = 19.98) for this parameter is out of range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the results of Hosseini & Masoome (2016) and Nikunj et al. (2017). The results obtained from the coefficients of structural equations based on the effect of advertising structure on value creation show that the value (t = 2.19) for this parameter is out of range. Therefore, it can be stated that the above assumption is confirmed with 95% confidence. The result of this hypothesis is consistent with the research results of Asadnejad et al, (2022). The results obtained from the coefficients of the structural equations based on the effect of the background conditions on the service provision processes show that the value (t = 7.12) for this parameter is estimated outside the range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the research results of Busca & Bertrandias (2020). The results obtained from the coefficients of structural equations based on the effect of Ambient characteristics on value creation show that the value (t = 4.99) for this parameter is out of range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the results of Hosseini et al., (2015) and Nikunj et al., (2017). The results obtained from the coefficients of the structural equations based on the effect of Ambient characteristics on recovery processes show that the value (t = 2.9) for this parameter is out of range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the results of Nikunj et al., (2017) and Asadnejad et al, (2022). The results obtained from the coefficients of structural equations based on the effect of marketing processes on value creation show that the value (t = 9.003) for this parameter is out of range. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the research results of Asadnejad et al, (2022). The results obtained from the coefficients of the structural equations based on the effect of value creation on the development of relationships show that the value (t = 27.97) was estimated out of range for this parameter. Therefore, it can be stated that the hypothesis of the researcher is confirmed with 95% confidence. The result of this hypothesis is consistent with the results of Michael et al., (2018) and Hollebeek et al, (2019).